1972
DOI: 10.1111/j.1440-1754.1972.tb01791.x
|View full text |Cite
|
Sign up to set email alerts
|

CHOLESTEROL AND THE CHILD: STUDIES OF THE CHOLESTEROL LEVELS OF BUSSELTON SCHOOL CHILDREN AND THEIR PARENTS1

Abstract: SYNOPSIS In 1964 as part of a population study, the blood cholesterols of 1,292 school children in the town of Busselton in Western Australia were examined. A gradual rise in the median value throughout school life was demonstrated in both boys and girls, with a pre‐adolescent rise comparable with similar studies elsewhere. In 1969 the cholesterol levels of the children with the highest, middle and lowest 5% levels in 1967 were repeated and showed a highly significant correlation, thus indicating that a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1974
1974
1991
1991

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…For girls the corresponding figures were: at birth, 1-9 (0.6); at 1 year, 4-7 (1-0); at 5 years, 4-6 (0.7); and at 11 years, 5-1 (0-7). The mean (SD) high density lipoprotein concentrations (mmol/l) for boys were: at 5, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] …”
Section: Introductionmentioning
confidence: 99%
“…For girls the corresponding figures were: at birth, 1-9 (0.6); at 1 year, 4-7 (1-0); at 5 years, 4-6 (0.7); and at 11 years, 5-1 (0-7). The mean (SD) high density lipoprotein concentrations (mmol/l) for boys were: at 5, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] …”
Section: Introductionmentioning
confidence: 99%
“…In children, precursors of cardiovascular risk factors can be The cholesterol and triglyceride measuring methods had previidentified. In several countries investigations in this field have ously been standardized by four European laboratories (24); they been recently accomplished (15,16,17,35,38), but results of were rechecked during the study. plasma lipoprotein lipids have been reported (6,10,21,32,40) in Serum apolipoproteins A and B were determined by electroimlimited numbers.…”
mentioning
confidence: 99%
“…In two epidemiological investigations of the serum cholesterol of school children [7,14], a low but positive correlation was found between the chol esterol values of the children and their parents. G o dfr ey el at.…”
Section: Discussionmentioning
confidence: 99%
“…G o dfr ey el at. [7] found that the cholesterol values of the mother is more related than that of the father to the cholesterol value of the child, and S tarr [14] found that the cholesterol value is a family characteristic (table 1). The present family material has been studied, as was that of S t a r r , with regard to the cholesterol value because types II A and B occur most frequently.…”
Section: Discussionmentioning
confidence: 99%